Local and systemic cytokine profiles in children with pneumonia-associated lung consolidation - Lin, Jilei; Chen, Jiande; Yuan, Shuhua; Tang, Mingyu; Yang, Guijun; Zhang, Huishan; Li, Wanlin; Zhao, Hui; Zhang, Jing; Zhang, Lei; Yin, Yong (Frontiers in Immunology, 2025)
ObjectiveLung consolidation (LC) in pediatric pneumonia could lead to complicated clinical outcomes, yet the underlying immunological mechanisms are not fully understood. This study aimed to investigate the roles of local and systemic cytokines in the development of pulmonary complications and disease progression in children with pneumonia-associated LC.DesignConducted at the Shanghai Children’s Medical Center, this study included 169 children admitted between June 2022 and October 2023.MethodsWe analyzed levels of fifteen cytokines in bronchoalveolar lavage fluid (BALF) and blood. Classification and regression tree (CART) analysis identified specific cytokines associated with pulmonary complications and hypoxemia.ResultsIn children with LC, most local cytokines were found at higher levels than systemic cytokines, with no apparent correlation between the two. Notably, an elevated level of IL-8 (≥ 6615 pg/ml) in BALF was associated with an increased risk of hypoxemia. Additionally, elevated levels of IL-4 and INF-γ in BALF were closely associated with the development of multi-segmental LC. Furthermore, elevated levels of IL-2R in BALF were significantly associated with the occurrence of atelectasis, in contrast to their levels in peripheral blood.ConclusionIL-4, INF-γ, IL-2R, and IL-8 levels in BALF are closely associated with pulmonary complications and disease progression in children with LC. Exploring targeted immunomodulatory therapies in these children may mitigate lung injury caused by excessive local inflammatory responses.